1970
DOI: 10.2136/sssaj1970.03615995003400010031x
|View full text |Cite
|
Sign up to set email alerts
|

Dust Deposition in Relation to Site, Season, and Climatic Variables

Abstract: Mean monthly dust deposition into standard traps for 14–37 mo at 14 locally nondusty sites east of the Rocky Mountains ranged from 17–459 kg/ha (15–410 lb/acre). Analyses of variance for 13 sites over 27 mo showed significant differences in dust rates, pH, oxidizable matter, and percent clay for sites and for months.Some late fall and winter months showed significantly lower rates than late spring and summer. The silt plus sand fraction tended to be lower and the percentages of oxidizables were higher for low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 0 publications
2
21
0
2
Order By: Relevance
“…For the Midwest, technical studies of dust production, transport, and deposition received large-scale federal funding after the dust bowl years (see, e.g., Chepil, 1957aChepil, , 1957bChepil and Woodruff, 1957). Results from a network of stations to monitor dust fall in the eastern United States were published by Smith et al (1970).…”
Section: Atmospheric Dust Sedimentationmentioning
confidence: 99%
“…For the Midwest, technical studies of dust production, transport, and deposition received large-scale federal funding after the dust bowl years (see, e.g., Chepil, 1957aChepil, , 1957bChepil and Woodruff, 1957). Results from a network of stations to monitor dust fall in the eastern United States were published by Smith et al (1970).…”
Section: Atmospheric Dust Sedimentationmentioning
confidence: 99%
“…Hence, more mica in the soil or loess will result in a lower K/Rb ratio. In Figure 5.6, The K/Rb vs. Ti/Nb ratios for the soils in this study show that despite the large amount of loess deposition in the Flint Hills reported by Smith et al (1970) (50 kg/ha/mo. ), these soils are not purely loess derived.…”
Section: -Element Ratios and Weatheringmentioning
confidence: 60%
“…The influx of wind-blown dust in the 1960s was calculated at 50kg/ha/month near Manhattan, Kansas, the municipality located directly between the two sites for this study (Smith et al, 1970).…”
Section: -Element Ratios and Weatheringmentioning
confidence: 99%
“…Area circunmediterránea Bücher et al (1975) Loye-Pilot et al (1986) Pye (1992) Mattsson et al (1996) Yaalon et al (1974) Ganor et al (1982) Area africana Pye (1987) Pye (1987) Drees et al (1993) Otras áreas Windom (1969) TilIer et al (1984 Free (1911) Soil Conservation Service (1962) Smith et al (1965) Smith et al (1970) Smith et al (1970) Smith et al (1970) Gile et al (1979) Muhs (1983) Rabenhorst et al (1984) Años muestreados 1984 1988-1990 1988-1994 1985-1989 1963-1964 1965-1970 1962-1965 Tasas (g.m-2 ·a-') et al., 1970). En el ámbito europeo también hay referencias de transporte de polvo sahariano, en puntos tan alejados como Rusia, Alemania o las Islas Británicas.…”
Section: Autorunclassified
“…La recogida sistemática de polvo atmosférico sólo se ha realizado en las últimas décadas, particularmente tras el impulso recibido por diversos trabajos, efectuados en regiones semiáridas y áridas de EE.UU., relacionadas con fenómenos climáticos y con el conocimiento de flujos de carbonatos en suelos (Gile et al, 1966;Smith et al, 1970;Schlesinger, 1982Schlesinger, , 1985. Estos seguimientos se han generalizado a otros lugares.…”
Section: Introductionunclassified